Effect of Different Fertilizers and Approaches on Nutrient Use Efficiency and Economics of Aerobic Rice Under Rice-Cowpea Cropping Sequence in Ecological Conditions of Karnataka, India - , Jayanthi T, Umesh H.R, Savitha Madappa, Latha H.S, Ashok L.B, Nunavath Umilsingh (Archives of Current Research International, 2024)
At the University of Agricultural Sciences, GKVK, Bengaluru, a field experiment was conducted in 2015-16 and 2016-17 to examine the impact of fertigation on the yield, nutrient usage efficiency, and economics of aerobic rice in an aerobic rice–cowpea cropping sequence. In a randomized block design, hybrid rice was tested in aerobic conditions with 16 treatments that were reproduced three times. The results indicated that significantly higher grain (62.98 q ha-1) and straw (85.26 q ha-1) yield of rice was recorded in 100% STCR dose through WSF at 8 DI. Similarly higher NRn (3.50 kg q-1) and NRp (0.86 kg q-1) of grain production in 100% STCR dose with WSF at 8 DI on contrary, higher NRk of 2.27 kg q-1 was noticed in 100% STCR with WSF at 4 DI. While higher AUE-N (32.51 kg kg-1), AUE-P (65.02 kg kg-1) and AUE-K (65.02 kg kg-1) were recorded in 30% RDF with WSF at 8 DI. The higher ACRE-N (78.60 %) was recorded with 100% RDF with WSF at 8 DI and higher ACRE-P (44.40%) was recorded with 30% RDF with WSF at 8 DI. Notably higher ACRE-K (132.51%) was recorded in 30% STCR with WSF at 8 DI. However, supplement of 30% STCR dose with WSF at 8 DI obtained notably higher IUE-N (35.05 kg kg-1), IUE-P (163.27 kg kg-1) and IUE-K ( 60.11 kg kg-1). Significantly higher PFP-N, P and K (261.23, 522.46 and 522.46, respectively) were recorded in 30% RDF with WSF at 8 DI. Among all treatments, 100% RDF through CF at 4 DI found significantly higher B: C ratio (2.74) during both years of pooled data.